Research of the demand for teachers - Petkus, Tomas; Karaliun, Ilona (Lietuvos matematikos rinkinys, 2014)
The demand for the nature science, mathematics and technologies teachers in Lithuania has been forecasted in this paper. This forecasting is a complex process because it is affected by many factors, such as the birth rate, staff numbers, teachers age, immigration and emigration, etc. The forecast is based on data from the Statistics Lithuanian, the register of teachers, the labour exchange. It is taking into account the current and predicted emigration, the wastage of the number of pupils,moving from a lower to a higher class, as well as the number of teachers in training.
Keywords: demand for the teachers; account of pupils; forecasting